Harvest : Chinese Photography Exposition. - Zheng, Gu; Art Scene China, Shanghai (Shanghai : Art Scene China, 2006)
Yi Luo, Bai ; You Tao, Cao ; Hao, Hong ; Yun He, Huang ; Jian, Jiao ; Yi Qing, Liu ; Yong Yin, Luo ; Jia Xin, Miao ; Xiao Chun, Miao ; Chen, Mu ; Yinong, Shao ; Ye, Tian ; Ningde, Wang ; Dan Wen, Xing ; Han, Zeng ; Feng, Zhu ; Hao, Zhu ; Hui, Zhang
Art Scene China, Shanghai, 2006
kunstcatalogus
Keywords: China